The Effect of Black Garlic Extract as a Curative Therapy on Increased Total Cholesterol in Obesity Model Rats - Shalsa Nabilla; Prima Adelin; Berri Ramadhoni; Letvimona; Rahma Triyana (Journal of Public Health Indonesian, 2026)
Obesity is a condition of excess body fat accumulation that often triggers an increase in total cholesterol levels in the blood, thereby increasing the risk of cardiovascular disease. Black garlic, a fermented garlic product, is known to contain bioactive compounds such as S-allylcysteine (SAC) which is effective in lowering cholesterol levels. Objective: To determine the effect of black garlic extract as a preventive therapy in obesity model rats induced by a high-fat and fructose diet. Method: The research method used an experimental design with a pre- and post-test group design approach. A total of 28 male Sprague Dawley rats were divided into four groups: negative control (standard diet AIN 93), positive control (high-fat and fructose diet), and two treatment groups each given black garlic extract at a dose of 1.6 ml/day and 0.8 ml/day. Total cholesterol levels were measured before and after the intervention using the spectrophotometric method. Data analysis used SPSS with the Independent t-test. Results: The results showed that administration of black garlic extract significantly reduced total cholesterol levels in the treatment group compared to the positive control group. A dose of 1.6 ml/day produced a greater cholesterol-lowering effect than a dose of 0.8 ml/day. Conclusion: Black garlic extract was effective in lowering total cholesterol levels in an obese rat model.